Extension of the distribution of Cochranella granulosa (Taylor, 1949) in Colombia and Ecuador: Ampliación de la distribución de Cochranella granulosa (Taylor, 1949) en Colombia y Ecuador - Barrio-Amorós, César L.; Forero-Cano, Andrés Mauricio; Reyes Serna, Felipe; Nieto, Raúl; Rombeaut, Corentin (Anartia, 2022)
Cochranella granulosa was described by Taylor (1949) from “Los Diamantes, one mile south of Guápiles, Costa Rica”, on the Caribbean versant of the Talamanca range of Central America. The species is well distributed from southern Honduras throughout scattered localities in Nicaragua, and on both versants of Costa Rica towards Panama (Köhler 2010). Recently the species has been reported from a single locality in Colombia, very close to the Panamanian border (Díaz-Ricaurte & Guevara-Molina 2020). From there, there is an apparent hiatus until Ecuador, where the species was reported also recently from a single locality in Jardín de los Sueños, Cotopaxi Province, the southernmost locality recorded for the species (Culebras et al. 2020). Guayasamín et al. (2020) reported a further locality from Ecuador, 4 km West of Río Durango, 232 m in elevation, in Esmeraldas Province (Museo de Zoología, Pontificia Universidad Católica del Ecuador, Quito, Ecuador: QCAZ 32769). Herein we report a second locality based on photographic evidence from Colombia, plus two other photographic registers from iNaturalist, and a third individual of the species for Ecuador. In addition, photographic documentation of an uncollected individual offers us the possibility to build a distribution map of the species and comment upon phenotypic variation.